Algiers–Paris Round Trips: Diasporic Pathways of a Public Civil Dissidence. Issue 3 (2nd July 2016) - Hadjab, Warda
ABSTRACT: The fourth term official announcement of the Algerian President provoked in February 2014 a microscale protest movement called "Barakat" (Enough!) in Algiers. The state repression of the pacific protesters triggered a political mobilization among the Algerians living in France, particularly in Paris. Through an Algiers–Paris round-trip analysis, this article sheds light on the political involvement of the Algerian protesters in Paris. It explores the new Algerian diaspora process experience in the Arab civil uprising context, post-2011, and its protean outlines and contributions to reshape (or not) the frontiers of nation, citizenship, political participation, and public debate.